1989
DOI: 10.1159/000185326
|View full text |Cite
|
Sign up to set email alerts
|

Intraglomerular Deposition of Coagulation-Fibrinolysis Factors and a Platelet Membrane Antigen in Various Glomerular Diseases

Abstract: The intraglomerular location of coagulation-fibrinolysis factors (CFF) and a platelet membrane antigen (glycoprotein IIb-IIIa; GPIIb-IIIa) was determined in 101 patients with various glomerular diseases. Renal biopsy specimens were examined by immunofluorescence microscopy, using antisera against fibrinogen/fibrin reactive antigen (FRA), cross-linked fibrin degradation products (XL-FDP), fibronectin (FN), factor XIH-subunit a (F-XIIIa), plasminogen (Pig), α2-plasmin inhibitor (α2-PI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
12
0
2
Order By: Relevance
“…Polymorphs, macrophages, monocytes and lymphocytes all have receptors for C3b [4]. The action of complement is enhanced by fibronectin and it initiates Fc and C3 receptor cell-mediated phagocytosis [5], The membrane attack complex and coagulation-fi brinolysis factors have previously been detected in the GBM and BC by immunofluorescence microscopy in membranous nephropathy [6][7][8]. Another study suggests that the immune deposits seen in stage 3 membranous nephropathy themselves trigger the C5b-9 complement sequence [9].…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphs, macrophages, monocytes and lymphocytes all have receptors for C3b [4]. The action of complement is enhanced by fibronectin and it initiates Fc and C3 receptor cell-mediated phagocytosis [5], The membrane attack complex and coagulation-fi brinolysis factors have previously been detected in the GBM and BC by immunofluorescence microscopy in membranous nephropathy [6][7][8]. Another study suggests that the immune deposits seen in stage 3 membranous nephropathy themselves trigger the C5b-9 complement sequence [9].…”
Section: Resultsmentioning
confidence: 99%
“…Platelets are sources of a number of mediators (for example platelet-derived growth factor) affecting mesangial function, capillary permeability and glomerular hemodynamics. In situ studies demonstrated an increased amount of platelets and coagulation cascade products in the glomeruli of patients with various forms of glomerulonephritis including IgAN and MGN [12, 13]. Furthermore, there is evidence supporting an involvement of the coagulation system in the pathogenesis of tubulointerstitial damage [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the glomeruli of patients with IgA-N, various coagulation-related and platelet membrane anti gens have been observed by immunofluorescent micro scopy [3,[5][6][7][8][9][10], However, only a few studies have at tempted to clarify the role o f intraglomerular coagulation and platelet aggregation in the progression of glomerular injury. The extent of segmental sclerosis is considered to be a prognostic factor in IgA-N [24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported on the intraglom erular localization of platelet-related antigens in renal disease [6,[8][9][10]. However, it is difficult to observe the precise status of platelets by immunofluorescence micro scopy or ordinary electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation